Technical report: the maximum horizontal length of ballistic projectile during volcanic eruption / Noor Maizatul Nazuha Mohamad, Syahirah Afiqah Mohd Taufik and Wan Nurelisha Aqia Wan Zaini - Mohamad, Noor Maizatul Nazuha; Mohd Taufik, Syahirah Afiqah; Wan Zaini, Wan Nurelisha Aqia (2016)
Nowadays, the eruption of the active volcanoes give a big impact to the resident around it. The residents around the volcanoes should know the maximum horizontal length of magma that will flow to avoid any casualties. This project are entirely on calculating the maximum horizontal length of the magma ejected during the eruption based on the types of volcano. This project specified on the special cases which is air drag (Cd) is equal to zero. It consider the spherical shape of the tephra that been burst out from the vent. The derivation started with the Volcanic Ballistic Projectile (VBP). VBP acting by the two forces namely gravitational attraction and drag against the climatic air. Next, one of the subsection from Vector Calculus which is Motion In Space (Velocity and Acceleration) being used. Newton's Second Law of Motion, F = ma is applied after the special cases. By considering the type of volcanoes, a result give a different range of maximum horizontal of the magma flowed. This is because of some factors affecting the surface of volcanoes which is the viscosity of the magma flowed. The low viscosity of the magma permits the magma should venture out down incline causing the least horizontal length of magma travel.